Foreword - Epure, Manuela (Journal of Economic Development, Environment and People, 2019)
Migration is a normal social phenomenon; people are leaving their home countries for many reasons, economic wealth-being, life-threatening conditions, social change, or political persecutions. The refugee crisis in Europe makes us rethink how new incoming cohorts of people can be supported not only for humanitarian reseasons but also to ensure them a long-term integration and become economic and social contributors to the receiving countries. From an economic point of view, migration is beneficial due to the incoming labor force brought into the receiving countries, filling the gaps existing in some industries across Europe. Migration inside EU, from a member state to another is normal, free movement of workers is encouraged and support by specific measures. Migration flows coming from outside EU, have created new challenges form member states: how many immigrants can be received in each country? A great debate aroused around the calculation of cota of incoming migrants to be acceptable. In 2018, 634.700 people applied for international protection and lodged in the EU, a 10% decrease compared with 2017, the main countries of origin were Syria, Afganistan, Iraq, Pakistan, and Iran. The first five receiving countries are Germany (222.560 refugees), Italy(128.850 refugees), France (99.360 refugees), Greece (58.650 refugees), United Kingdom (33.780 refugees)[1].